Linguistic and Cultural Analysis of Translation Techniqies in the Process of Adaptation of an English Series - N. V. Stepanova; Ye. Yu. Sinitskaya (Дискурс, 2023)
Introduction. This article is devoted to the study of the specifics of stylistic techniques within translation of non-equivalent and culturally marked lexemes. The relevance of the research is determined by the fact that a rapidly developing films production market requires a high-quality adaptation of foreign films for other cultures. There is a need for a comprehensive study on adaptation mechanisms of various ethno-cultural phenomena displayed during translation from one language to another.Methodology and sources. This research was conducted in the context of a linguostylistic approach to the text analysis. Following methods were applied: comparative, directional sampling, classification, text interpretation, component analysis of lexical units, as well as the methods of contextual, semantic-cognitive and linguocultural analysis. The research is based on the transformations classifications by L.K. Latyshev and L.V. Solonovich, as well as the classification of culture-specific concepts by V.S. Vinogradov. The British-American series “Good Omens” was chosen as the research material. The analysis was conducted on the basis of the officially published script translated by Y. Poleshchuk.Results and discussion. Linguocultural adaptation of a foreign language work includes complex translation and stylistic transformations. In most cases, stylistic transformations within the series adaptation are related to idioms, metaphors and other expressive lexemes, due to discrepancies in the system of images between languages and due to the ways of conveying emotional tones in Russian and English. Nevertheless, it is not recommended to abuse the adaptation of culture-specific concepts, otherwise the meaning and national peculiarities transmitted through the original text will be lost. In the context of translating a series, this issue can be particularly acute due to inseparable connection between image and text.Conclusion. Cinematographic works, distinguished by their inseparable combination of audio and visual images, are able to unite cultures, to be a tool in the study of other cultures and languages. A pragmatic attitude towards a foreign language recipient requires a responsible approach to adapting the film text translation. The key role in this process is played by stylistic translation transformations, which are related to culturally marked lexemes, allusions, and other stylistic devices.